Experimental Study on the Interfacial Bonding Performance of a New Steel Bridge Deck Interface-Bonding Agent - Chaohua Zhao; Ya Li; Zhijian Yi; Kang Su (Advances in Materials Science and Engineering)
The construction of steel deck pavements is still considered difficult worldwide, and interfacial bonding is a major factor influencing this construction. With the recent developments in the field of pavement materials, high-performance cement-based concrete is used to construct steel bridge deck pavements. However, ensuring adequate interface-bonding strength remains particularly complex and difficult. In this study, with the aim of striking the right balance between rigidity and flexibility, an interface-bonding material was formed using modified epoxy resin, cement, and rubber powder. Polymer lattice porous concrete was used as the paving material, and the interface-bonding effect was studied experimentally by employing three methods using the material: pull-off, dual-interface shear, and flexural tensile tests. The results showed that (1) the interface pull-off strength was higher than 4 MPa, that is, higher than twice that of epoxy asphalt pavements used currently on steel bridge decks, and the failure surface was located on the pavement material rather than on the bonding interface; (2) the interface flexural strength and tensile strength were significantly higher than those of epoxy asphalt at room temperature and those of the ordinary epoxy resin; (3) the dual-interface shear strength was nearly four times higher than that of epoxy asphalt. Therefore, the modified epoxy resin composite interface-bonding material suggested in this study is an excellent bonding material that can serve as a reference for interface-bonding of steel bridge deck pavements.